Promoting breastfeeding in Chinese women undergoing cesarean section based on the health belief model: A randomized controlled trial. Issue 28 (10th July 2020) - Hu, Lei; Ding, Tingting; Hu, Juan; Luo, Biru
Abstract: Background: The high rate of cesarean section is an important factor affecting breastfeeding in China. To improve the nation's current situation of breastfeeding, promoting breastfeeding in women undergoing cesarean section is essential. Objective: To explore the effects of health belief model-based interventions on breastfeeding knowledge, breastfeeding behaviors, and breastfeeding satisfaction of Chinese cesarean women. Methods: A total of 346 cesarean section women were enrolled in the randomized controlled trial conducted at a center in Chengdu, China, between July 1, 2018 and August 31, 2018. While the control group (n = 173) received conventional breastfeeding guidance only, the intervention group (n = 173) received additional interventions based on the health belief model. Questionnaires were distributed to assess breastfeeding knowledge, breastfeeding behavior, and breastfeeding satisfaction at discharge, 42 days postpartum, and 4 months postpartum, respectively. Results: At discharge from hospital, the breastfeeding knowledge score of the intervention group was higher than that of the control group ( Z = −11.753, P < .001). The exclusive breastfeeding rates in the intervention group at the time of discharge, 42 days postpartum, and 4 months postpartum were 67.3%, 60.7%, and 52.9%, respectively, while those of the control group were 41.2%, 41.6%, and 40.4%, respectively. The differences were statistically significant ( χ 2 = 23.353, P < .001; χ 2 = 11.853, P < .001; χ 2 = 4.805, P = .03). The breastfeeding satisfaction of the intervention group was also higher than the control group at the time of discharge, 42 days postpartum and 4 months postpartum ( t = 4.955, P < .001; t = 3.051, P = .002; Z = −3.801, P < .001). Conclusion: The health belief model-based interventions can effectively increase breastfeeding knowledge for Chinese cesarean women and improve their breastfeeding behaviors and breastfeeding satisfaction within 4 months after delivery. Clinical Trial Registration: ChiCTR1900026006 <http://www.chictr.org.cn/usercenter.aspx >